Fuel price differentials and car ownership: A spatial analysis of diesel cars in Northern Ireland. (August 2018) - Morton, Craig; Lovelace, Robin; Philips, Ian; Anable, Jillian
Highlights: Northern Ireland has a distinctly higher rate of diesel car ownership. The Republic of Ireland has historically had cheaper diesel fuel prices. Nearness to the border is linked with higher diesel car ownership. 4% of diesel car ownership in the North is linked to cheaper fuel availability in the Republic. Abstract: Car fleets across much of Europe have undergone a process of dieselisation over the past 20 years. Understanding the factors driving this process is therefore important for sustainable transport policy, with implications for how governments steer their national car fleets towards ultra-low emission vehicles in the future. At a general level, this paper contributes to this wider body of work which aims to understand the factors which led to the transition from petrol to diesel. Specifically, the paper investigates whether the availability of relatively cheap diesel fuel in the Republic of Ireland affected the rate of diesel car ownership in Northern Ireland. A geographic approach is used, which involves generating spatial variables measuring nearness to the Republic of Ireland and comparing these with the proportion of the local car stock that is fuelled by diesel. A series of spatial regression models are specified to determine if this association between nearness to the Republic and diesel ownership persists after accounting for the effect of socioeconomic, travel, and household characteristics. The results support the hypothesis that the availability of cheaper fuel in the Republic of Ireland is not only generating fuel-tourism, but is also affecting the structure of the car fleet registered in Northern Ireland. The findings are relevant beyond the case study and imply that the structure of a country's car fleet is not only dependent on domestic policies, but is also affected by the policies of neighbouring countries.